Explaining the visibility of EU citizens: a multi-level analysis of European Union news. Issue 2 (16th November 2015) - Walter, Stefanie
Abstract : This article analyses the visibility of European Union (EU) citizens in EU news during the 2009 European Parliament election. It argues that the presence of EU citizens in EU news is vital for responsiveness of European governance. First, the theoretical notion of EU citizens is considered. Next, a new way of defining EU citizens is proposed: EU citizens are divided into national and supranational EU citizens. The visibility of EU citizens in EU news of 27 EU member states is analysed aiming to explain cross-country differences. The paper is based on a large-scale content analysis of TV and newspaper articles gathered during the 2009 European Parliament election. To explain different levels of visibility, a multi-level analysis is carried out. The results suggest that EU citizens are visible in the EU news, yet, their presence strongly varies across countries. The findings indicate that explanations for different levels of visibility can be found at both the media and country level.